2010
DOI: 10.1227/01.neu.0000359224.75185.43
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Approach to the Infratemporal Fossa

Abstract: Endoscopic exposure of the infratemporal fossa is feasible. Using the combination of the endonasal and Caldwell-Luc approaches for direct transmaxillary access significantly extended exposure, allowing safe and effective resection of infratemporal fossa lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
116
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 37 publications
1
116
0
4
Order By: Relevance
“…Several transmaxillary approaches have been used in the treatment of retromaxillary lesions. 9,14 Our data show that the sublabial approach provides the best horizontal working space, and the endonasal approach has the least horizontal working space; therefore, a sublabial approach may be superior in the case of tumors that extend in the same axial plane. In addition, we found that the transseptal approach has the least vertical working space; as a result, it may not be the best option in the case of tumors or lesions that extend in the same sagittal plane.…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…Several transmaxillary approaches have been used in the treatment of retromaxillary lesions. 9,14 Our data show that the sublabial approach provides the best horizontal working space, and the endonasal approach has the least horizontal working space; therefore, a sublabial approach may be superior in the case of tumors that extend in the same axial plane. In addition, we found that the transseptal approach has the least vertical working space; as a result, it may not be the best option in the case of tumors or lesions that extend in the same sagittal plane.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, we found that the transseptal approach has the least vertical working space; as a result, it may not be the best option in the case of tumors or lesions that extend in the same sagittal plane. The approaches we describe in this study were previously described with a detailed anatomical overview, 9,19 but an analysis of the exposed working space, including the surgical freedom and the area of exposure, has not been previously described. These concepts are important in planning the appropriate surgical approach for a specific lesion and for understanding the limitations of each of the approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations